Monetary policy, rudimentary financial markets and rapid goods market adjustment - Singh, Thomas B. ([Caribbean Centre for Monetary Studies] [St. Augustine]TT, 2002)
Discusses the importance of the state of financial market development to the adjustment mechanism. Presents a review of the standard Keynesian adjustment mechanism and discusses the determination of output and the interest rate. Focuses on the relatively rapid goods market adjustment when financial markets are rudimentary and also when inventory costs are high. Comments on the potential applicability of the analysis to the open economy and even to developed countries, especially in the wake of recent corporate accounting scandals.